EMOTIONAL FACTOR AS A MEANS OF QUALITY ASSURANCE OF THE EDUCATIONAL PROCESS IN SECONDARY AND HIGHER SCHOOLS (Pedagogy of Higher and Secondary Education, 2009)
The evotional factor as a means of guaranteeing the quality of a modern educational process in the basic and high school is substantiated in the article.